The Relationship of History of Pre Eclampsia (PE) with the Incidence of Pre Eclampsia (PE) in Pregnant Women in the Delivery Room of RSD “S” Jember - Umami, Riza (Journal of Midwifery Science: Basic and Applied Research, 2025)
Preeclampsia as one type of pregnancy hypertension that needs to be watched out for, which is a specific hypertensive disease due to pregnancy accompanied by multisystem disorders and arises after 20 weeks of gestation which can cause morbidity and mortality worldwide both in the mother and fetus. Preeclampsia is the most common complication of pregnancy with a total of 14,128 cases (East Java Health Office Profile, 2022). The cause of preeclampsia is unknown, but a history of preeclampsia is one of the risk factors. Pregnant women with a history of preeclampsia contribute 20% of the risk of preeclampsia in subsequent pregnancies. This study aims to determine the relationship between the history of preeclampsia and the risk of preeclampsia in the maternity ward of RSD “S” Jember and analyze the strength of the relationship between the two. The research design used descriptive analytic with retrospective crossectional approach. The study population was 636 maternity mothers, with a total sampling technique of 343 respondents. Data were collected using secondary data and analyzed using the Chi Square test and the Coefficient of Contingency.The results showed that there was a relationship between the history of preeclampsia and the incidence of preeclampsia with ρ-value = 0.000 α 0.05 and the correlation value of 0.452 with moderate closeness, which means that mothers who have a history of preeclampsia can cause preeclampsia in the next pregnancy.To prevent the incidence of preeclampsia, midwives can provide comprehensive care through the implementation of integrated ANC.Midwives are expected to be able to screen for preeclampsia appropriately, make promotive efforts to mothers and families regarding pregnancy preparation such as paying attention to the optimal age of the mother to become pregnant, set the distance of pregnancy 2 and set the maximum number of births 4.Keywords:Preeclampsia; History of Preeclampsia